Empirically supported psychodynamic psychotherapy for common mental disorders–An update applying revised criteria: Systematic review protocol - Leichsenring, Falk; Abbass, Allan; Heim, Nikolas; Keefe, John R.; Luyten, Patrick; Rabung, Sven; Steinert, Christiane (Frontiers in Psychiatry, 2022)
The approach of evidence-based medicine has been extended to psychotherapy. More than twenty years ago, criteria for empirically supported psychotherapeutic treatments (EST) were defined. Meanwhile a new model for empirically supported psychotherapeutic treatments has been proposed. While the empirical status of psychodynamic therapy (PDT) was assessed in several reviews using the previous criteria, the proposed new model has not yet been applied to PDT. For this reason, we will carry out a systematic review on studies of PDT in common mental disorders applying the revised criteria of ESTs. As suggested by the new model we will focus on recent systematic quantitative reviews. A systematic search for meta-analyses on the efficacy of PDT in common mental disorders will be carried out. Meta-analyses will be selected and evaluated by at least two raters along the criteria of the new proposed model. In addition, systematic reviews and individual studies addressing mechanisms of change in PDT, effectiveness under real-world conditions, cost-effectiveness and adverse events will be systematically searched for and evaluated. Finally, quality of evidence, the extent to which benefits exceed harms and strength of recommendations will be assessed per disorder using GRADE.